A LINGUOCULTUROLOGICAL STUDY OF THE CONCEPT OF COMMUNICATION IN ENGLISH AND UZBEK LANGUAGES - Abdujabborova , Shoxista (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article provides a comprehensive linguoculturological analysis of the concept of communication in English and Uzbek languages. It examines the interrelation between language and culture through communicative behavior, speech strategies, and national mentality. The findings reveal that English communication is characterized by individualism, directness, and clarity, whereas Uzbek communication is shaped by collectivism, respect, and indirect expression.